Analytical Performance Evaluation of Different Switch Solutions - Francisco Sans; Eric Gamess (Journal of Computer Networks and Communications)
The virtualization of the network access layer has opened new doors in how we perceive networks. With this virtualization of the network, it is possible to transform a regular PC with several network interface cards into a switch. PC-based switches are becoming an alternative to off-the-shelf switches, since they are cheaper. For this reason, it is important to evaluate the performance of PC-based switches. In this paper, we present a performance evaluation of two PC-based switches, using Open vSwitch and LiSA, and compare their performance with an off-the-shelf Cisco switch. The RTT, throughput, and fairness for UDP are measured for both Ethernet and Fast Ethernet technologies. From this research, we can conclude that the Cisco switch presents the best performance, and both PC-based switches have similar performance. Between Open vSwitch and LiSA, Open vSwitch represents a better choice since it has more features and is currently actively developed.